Beyond Coexixtence: Intersecting Realms of Faith and Policy in Mentawai, Indonesia - Dwi Wahyuni; Fadhiil Novriadi Pratama; Julita Lestari; Anjali Sabna; Martalia Martalia (Khazanah Sosial, 2024)
This study explores the relationship between the indigenous religion of the Mentawai people, Arat Sabulungan, world religions (Christianity, Catholicism, and Islam), and the state, focusing on intersubjective recognition among these entities. The research employs a qualitative ethnographic approach, conducted in Matotonan village, South Siberut subdistrict, West Sumatra. Primary data were gathered through semi-structured interviews with key informants and observations, while secondary data included literature reviews of relevant journal articles, books, research reports, and news. The findings reveal the complexity and nuances of religious conversion, the socio-cultural dynamics influencing the negotiation process of Arat Sabulungan and world religions, and the role of state policy in shaping the religious landscape and identity of the Mentawai people. This article demonstrates that the socio-cultural life of the Mentawai people, especially in Matotonan village, shows that recognition of Arat Sabulungan extends beyond intercultural relations into the anthropological realm. Followers of Arat Sabulungan (Sikerei), world religions, and government employees have constructed themselves as subjects through intersubjective recognition. This research contributes to understanding the complex dynamics between indigenous religions, world religions, and state policies. It applies Axel Honneth's theory of intersubjective recognition, highlighting the need for inclusive policies, cultural education, and legal recognition to support and preserve indigenous religions like Arat Sabulungan.